85.9k views
2 votes
Use substitution to solve the

following system of equations.
-2x + 4y = -18 AND x = y + 3

User Inspirednz
by
5.2k points

2 Answers

3 votes

Answer:

x = -3 ; y = -6

Explanation:

x = y + 3

-2x + 4y = -18

-2(y+3) + 4y = -18

-2y -6 + 4y = -18

2y = -12

y = -6

x = -6+3

x = -3

User John Leimon
by
4.6k points
4 votes

Answer:

x = -3 y = -6

Explanation:

x = y + 3

x - 3 = y

-2x + 4(x - 3) = -18

-2x + 4x - 12 = -18

2x = -6

x = -3

x = y + 3

-3 = y + 3

-6 = y

User Joseph Saunders
by
5.2k points